PHYSICO-CHEMICAL ANALYSIS AND IMPACT OF DIFFERENT SHODHANA METHODS ON GUGGULU (AYUSHDHARA, 2020)
Objective: Guggulu is one of the important Dravya (drug) used in Ayurvedic formulations since ancient time which means “Protection against diseases”. Ashuddhaguggulu has physical and chemical impurities which need to be eliminated before using in formulation by Shodhana. The present study was conducted to evaluate and compare the effect of different Shodhana methods i.e., Dolayantra Shodhana and dissolving Shodhana on properties of Guggulu by employing various physic-chemical and chromatographic methods. Method: Physicochemical screening was done by evaluating ash, Acid Insoluble Ash, Loss on Drying, Water Soluble Extractive and Alcohol Soluble Extractive. Chromatographic analysis was performed to estimate guggulsterone (E and Z) content, using High Performance Liquid Chromatography (HPLC). Result: The Physico-chemical studies showed decrease in LOD, Ash and Acid Insoluble Ash content and increase in extractive values such as Alcohol Soluble Extractive of Guggulu after Shodhana process. The HPTLC analysis showed significant change in guggulsterone (E and Z) content in Guggulu after Shodhana process Conclusion: This study helps to understand the effect of different Shodhana methods on the efficacy of drug. In this study, we established qualitative profile of Shodhit Guggulu in terms of physicochemical parameters and phytochemical content by HPLC.